Informasi Kesehatan Pendengaran Pada Bayi dan Anak Melalui Program Kesehatan TVRI NTB - Yuliyani, Eka Arie; Putu Aditya Wiguna; Ika Primayanti; Anak Agung Ayu Niti Wedayani (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
As one of the modern media, television has an important role in conveying various information, including about the world of health. Through attractive and audio-visual displays, television can make it easier for people to receive the health information conveyed. Commemorating world hearing day, TVRI NTB station collaborates with Unram Hospital to provide health education through the "Sehat and Bugar" program with the theme "The Importance of Screening for Hearing Loss in Babies and Children". The aim of implementing this health program is to provide an understanding of the importance of hearing detection in babies and children as early as possible and to increase the knowledge of the NTB community regarding the growth and development of babies and children, especially regarding the ability to hear and speak according to their age. This event was well received by the community. These results can also be seen on Live Streaming which has been watched 121 times and can be used as an evaluation for similar activities in the future